College social insertion: an investigation based on the minimum social atom - Auad, Juliana Cal; Conceição, Maria Inês Gandolfo (Paidéia (Ribeirão Preto), 2008)
It is evident through history that disabled individuals occupy marginal positions and their insertion depend, in great part, on the social context. This study aims to investigate the social networks of college students with disabilities from a psychodramatic point of view. To achieve such goal, a new instrument called minimal atom, was created. This instrument was based on Moreno's social atom theory and Sluzki's minimal map. The interview and instrument were applied to seven students with physical disabilities. Results indicate that people with disabilities develop different roles in their families and at work/college. The university seems to be a place where these students can test their limits and develop friendships. The major difficulty for their inclusion in the university is related to their ability of moving around the campus. There is a clear need of supporting public policies for college inclusion criteria.